2019
DOI: 10.4236/jbm.2019.72009
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Reperfusion Ischemia and Use of Elastic Tourniquet

Abstract: Introduction: In humans, it has not been established that the use of elastic tourniquet (ET) during myomectomies, whose delivery times do not exceed 90 minutes, which is responsible for ischemia reperfusion (I/R) systemic. Objectives: To study the plasma variations of markers of I/R during myomectomies performed with ET, whose exposure time does not exceed 90 minutes. Population and methods: Plasma créatinin phosphokinase kinase (CPK) and gluthatione peroxydase (GPX) levels of patients with ET myoma (M + G +, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 47 publications
(65 reference statements)
1
9
1
Order By: Relevance
“…On the other hand, the fact that the CmNgb of CG + is greater than that of CG − allows us to discuss the intensity of expression of Ngb during severe chronic glaucoma (CG) compared to other situations of nervous system suffering (NS). Indeed, in the CG + population of this study, CmNgb was 8-fold higher than that found by Ovono et al in a study of newborns suffering of anoxo-ischemic encephalopathy syndrome (4.09 ng/ml versus 0.50 ng/ml) [46].…”
Section: Comparison Of Biological Variables In Patients With Severe Gcontrasting
confidence: 69%
See 3 more Smart Citations
“…On the other hand, the fact that the CmNgb of CG + is greater than that of CG − allows us to discuss the intensity of expression of Ngb during severe chronic glaucoma (CG) compared to other situations of nervous system suffering (NS). Indeed, in the CG + population of this study, CmNgb was 8-fold higher than that found by Ovono et al in a study of newborns suffering of anoxo-ischemic encephalopathy syndrome (4.09 ng/ml versus 0.50 ng/ml) [46].…”
Section: Comparison Of Biological Variables In Patients With Severe Gcontrasting
confidence: 69%
“…To do this, a Human NGB ELISA kit TM (N˚ E-EL-H1768) was used. The manual dosage procedure was conducted according to a protocol based on previous studies [40] [46] [47] [48]. The optical density was measured on a Biorad  PR 3100 TM reader.…”
Section: Biological Methods -Blood Collection and Conditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…The time of hospitalization was modified by the presence of a postoperative complication such as anemia, and a delay in return of bowel function. Other complications have been described in the literature [23] and the possibility of pregnancy after abdominal myomectomies [24,25].…”
Section: Discussionmentioning
confidence: 99%